1978
DOI: 10.1056/nejm197804132981501
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Treated Course of Usual and Desquamative Interstitial Pneumonia

Abstract: Patients with confirmed interstitial pneumonia were initially classified histologically into "desquamative" (n = 40) and "usual" (n = 53) types, and followed for one to 22 years. Both the diagnosis and the extent of fibrosis affected the course and response to therapy. Mortality in desquamative interstitial pneumonia was 27.5 per cent, and mean survival 12.2 years, as compared with 66.0 per cent and 5.6 years in usual interstitial pneumonia (P less than 0.01). Without treatment, 21.9 per cent with the desquama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
375
3
21

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 736 publications
(413 citation statements)
references
References 30 publications
14
375
3
21
Order By: Relevance
“…withtemporal heterogeneity [13]. Desquamative interstitial pneumonia is much less common but has a better prognosis than usual interstitial pneumonia, with a good responseto corticosteroids [13,15]. Its patho logic hallmark is diffuse intraalveolar mac rophage accumulation [13].…”
Section: Foamy Cell Collections In Alveolar Spacesmentioning
confidence: 99%
“…withtemporal heterogeneity [13]. Desquamative interstitial pneumonia is much less common but has a better prognosis than usual interstitial pneumonia, with a good responseto corticosteroids [13,15]. Its patho logic hallmark is diffuse intraalveolar mac rophage accumulation [13].…”
Section: Foamy Cell Collections In Alveolar Spacesmentioning
confidence: 99%
“…diopathic pulmonary fibrosis (IPF) is a chronic progressive interstitial lung disease (ILD) of unknown cause, resulting in severe morbidity and death due to progressive respiratory failure [1], usually within 3-5 yrs [2][3][4][5]. Prognostic factors that have been variably associated with survival include age [6], smoking status [7], sex [8], resting pulmonary function [9], histopathology score [7], fibrotic score based on high-resolution computed tomography [10,11], and initial response to treatment with corticosteroids [10].…”
mentioning
confidence: 99%
“…After discontinuation of the steroid therapy, no recurrence was detected, and the long‐term prognosis is considered good. As Carrington et al 2 previously reported, the extent of lung fibrosis is thought to be important in the prognosis of DIP. Further accumulation of cases and investigation are needed.…”
Section: Discussionmentioning
confidence: 91%